1998
DOI: 10.1200/jco.1998.16.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognostic factors in newly diagnosed acute promyelocytic leukemia treated with all-trans retinoic acid and chemotherapy. Japan Adult Leukemia Study Group.

Abstract: Our results show that age, hemorrhagic diathesis, and initial leukocyte count are prognostic factors for APL treated with ATRA followed by intensive chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
129
2
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(140 citation statements)
references
References 34 publications
3
129
2
3
Order By: Relevance
“…Most large clinical trials have not included CD34 immunophenotypic data in their published reports [1,4,5,7,10], and although a trend toward a poor outcome was noted in our study, we were unable to demonstrate a statistical difference in the survival outcome of CD34-positive and CD34-negative cases in our small cohort. These considerations suggest that future large trials in APL should include CD34 measurement to determine if the presence of a proportion of CD34 + APL blasts at presentation is an independent adverse prognostic marker.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Most large clinical trials have not included CD34 immunophenotypic data in their published reports [1,4,5,7,10], and although a trend toward a poor outcome was noted in our study, we were unable to demonstrate a statistical difference in the survival outcome of CD34-positive and CD34-negative cases in our small cohort. These considerations suggest that future large trials in APL should include CD34 measurement to determine if the presence of a proportion of CD34 + APL blasts at presentation is an independent adverse prognostic marker.…”
Section: Discussioncontrasting
confidence: 80%
“…Several studies have consistently demonstrated that a presenting WBC count (greater than 5 × 10 9 /L or 10 × 10 9 /L) correlates with an inferior clinical outcome in APL [1,4,5,7,8]. Feneaux et al [5] have shown that older age (P ‫ס‬ 0.006) and higher WBC count upon inclusion (P ‫ס‬ 0.02) are predictive of increased risk of early death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 This experience, reported by our group, included a small patient series receiving heterogeneous therapies containing ATRA. Results from this study and those pooled out from recent large multicenter ATRA trials including elderly patients, 7,8,10,12,14 reported high CR rates and prolonged survival, in marked contrast with the extremely poor outcome commonly observed for patients in the same age group affected by other AML forms. 17 However, as compared to younger APL patients, elderly ones had less favorable outcome, mainly because of poor tolerance to intensive chemotherapy rather than to the occurrence of resistant or more aggressive disease.…”
Section: Introductionmentioning
confidence: 55%
“…4,5 The introduction of ATRA and its combination with chemotherapy has led to considerable improvement in the disease outcome by allowing significantly higher complete remission (CR) and disease-free survival (DFS) rates with respect to the pre-ATRA era. [6][7][8][9][10][11][12][13][14][15] As to APL in the elderly, to the best of our knowledge only one study specifically focused on this subset has been published to date. 16 This experience, reported by our group, included a small patient series receiving heterogeneous therapies containing ATRA.…”
Section: Introductionmentioning
confidence: 99%